Efektivitas Peran Bawaslu Dalam Penyelesaian Sengketa Pemilu Melalui Mekanisme Hukum Acara MK - Anindya Paramesti Kusumo; Mega Dewi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The role of the General Election Supervisory Agency (Bawaslu) in resolving electoral disputes through legal procedures at the Constitutional Court (MK) is crucial for maintaining integrity and justice in the democratic process in Indonesia. This research aims to analyze the effectiveness of Bawaslu's role in resolving electoral disputes by identifying the factors that influence its performance and the challenges it faces. The research method used is a qualitative approach through document studies, which includes laws, regulations, as well as Bawaslu's annual reports and MK's decisions. The results of the study show that the obstacles faced by Bawaslu include limited resources, political intervention, and low public legal awareness. Although Bawaslu plays a role in preventing violations and resolving disputes, the inconsistency between Bawaslu's decisions and MK's rulings indicates the need for improved coordination among institutions. Recommendations for enhancing Bawaslu's effectiveness include capacity building, improving inter-agency coordination, increasing transparency, public education, and utilizing information technology. This study is expected to contribute to the development of a better and fairer electoral system in Indonesia.